2019
DOI: 10.1007/s11235-019-00571-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of downlink and uplink decoupled access in clustered heterogeneous cellular networks

Abstract: The performance of heterogeneous cellular networks (HCNs) is typically analyzed with the assumption that the users connect with the same base station in uplink and downlink. However, recent investigations have shown that downlink-uplink decoupling (DUDe) can provide network performance gains relative to the conventional coupled access. Many authors have evaluated HCN performance while assuming that the network users are distributed according to a homogeneous Poisson point process (HPPP). However, the HPPP cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…1 Following Slivnyak theorem, a typical user at origin leads to simplified statistical properties of an independent homogeneous Poisson point process (IHPPP) [9]. 2 The terms open loop power control and FPC are used interchangeably in this paper.…”
Section: B Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Following Slivnyak theorem, a typical user at origin leads to simplified statistical properties of an independent homogeneous Poisson point process (IHPPP) [9]. 2 The terms open loop power control and FPC are used interchangeably in this paper.…”
Section: B Related Workmentioning
confidence: 99%
“…Moreover, for each point j ∈ φ M , all the points of φ S A c M (j, d 1 ) are removed. Hence, the effective density of SBSs in the proposed model is given as pλ S , where p = exp(−λ M π d 2 1 ) [30].…”
Section: A Network Layout With Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in the DL, a T-UE is allowed to be associated with a HAP while, associated with a LAP in the UL, if the decoupled access is permitted. In [19]- [21], it was shown that under the decoupled access, the coverage performance is significantly better when comparing to the without the decoupled access.…”
Section: Introductionmentioning
confidence: 99%